2014
DOI: 10.2989/16085906.2014.952652
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the low uptake of adult male circumcision for the prevention of HIV transmission in Swaziland

Abstract: Swaziland is currently experiencing the worst impact of HIV and AIDS of any country in the world. In an effort to curb further spread of the virus, the country adopted mass male circumcision (MC) as recommended by the World Health Organization in 2007. Despite intense campaigns to promote the procedure over the past three years, the uptake of circumcision remains very low for reasons that are not very clear. The purpose of this study was to explore the reasons for the low uptake of MC in Swaziland despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…A qualitative study in Zimbabwe found that circumcision was perceived as an ‘alien culture’ and associated with satanic rituals . In Swaziland, there is a low uptake of voluntary medical male circumcision because of fear of the operation, perceived lack of benefit of circumcision and impatience with regard to the healing time . Thus, advertising and medical promotion of voluntary medical male circumcision are essential.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in Zimbabwe found that circumcision was perceived as an ‘alien culture’ and associated with satanic rituals . In Swaziland, there is a low uptake of voluntary medical male circumcision because of fear of the operation, perceived lack of benefit of circumcision and impatience with regard to the healing time . Thus, advertising and medical promotion of voluntary medical male circumcision are essential.…”
Section: Discussionmentioning
confidence: 99%
“…In Zambia, especially in the Copperbelt and Lusaka provinces, and in Swaziland, the contribution of never married men was very high, a finding that is partly explained by the low prevalence of circumcision in these countries [ 52 ]. Findings from studies investigating the determinants of uptake of voluntary medical male circumcision in these two countries should inform its scale up [ 53 56 ], and strategies such as early infant circumcision [ 57 , 58 ] or circumcision among adolescents through school programmes [ 59 ], which are likely to have higher acceptability, should be promoted [ 60 ]. Never married women were also disproportionately affected in Swaziland compared to their population size (see S2 Fig ), and similarly in Zambia, Gabon, the Southern province in Malawi, and Kigali City and the South province in Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar situation in Swaziland, male circumcision recipients were incentivized to undergo the procedure with spice packets and promotional items from a spice company. This led to a rumor that foreskins were an ingredient in the spice mixture [ 40 ]. It is difficult to know if these misconceptions might be a consequence of misinterpreted incentivization practices or international, Internet-based anti-circumcision campaigns.…”
Section: Discussionmentioning
confidence: 99%